Dietary Patterns are Related to the Incidence of Anemia in Adolescent Girls - Mia Ardina; Anas Rahmad Hidayat; Siti Fadhilah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Anemia in adolescent girls is a significant public health problem, especially in developing countries like Indonesia. This study aims to analyze the relationship between dietary patterns and the incidence of anemia in adolescent girls in Bogor Regency. The population in this study were adolescent girls aged 11–13 years who were selected through simple cluster sampling technique. Data were collected using a structured questionnaire and hemoglobin level measurements to determine anemia status. The instrument used was a dietary questionnaire with a validity test (r count = 0.23901 <0.36 1) and the reliability of the dietary questionnaire Cronbach's alpha value = 0.8346 (>0.6). Data analysis was performed using chi-square statistical tests and logistic regression. Adolescents with poor dietary patterns were the most likely to experience anemia, amounting to 125 adolescents or 42%. The chi-square test obtained a p-value = 0.001 (p <0.05), meaning there is a relationship between dietary patterns and the incidence of anemia in adolescent girls in Bogor Regency in 2025. Adolescents with knowledge of balanced diets tend to have a lower risk of experiencing anemia.